Indigenous Plots in Twenty-First Century Latin American Cinema - González Rodríguez, Milton Fernando (European Review of Latin American and Caribbean Studies, 2024)
Indigenous Plots in Twenty-First Century Latin American Cinema, by Maria Chiara D’Argenio, Springer, 2022